Attitudes towards job protection legislation: Comparing insiders and outsiders in Finland, Norway and Sweden. (December 2016) - Svalund, Jørgen; Saloniemi, Antti; Vulkan, Patrik
This article investigates employees' attitudes towards job protection legislation and attitudinal differences between employees with different levels of job security. National surveys from three Nordic countries, using different measures of insider–outsider positions in the labour market, do not support the assumption that outsiders (those with insecure jobs) prefer laxer job protection legislation. On the contrary, workers in secure jobs seem more likely to prefer laxer regulation.